Sex-driven variability in TSPO-expressing microglia in MS patients and healthy individuals - Laaksonen, Sini; Saraste, Maija; Nylund, Marjo; Hinz, Rainer; Snellman, Anniina; Rinne, Juha; Matilainen, Markus; Airas, Laura (Frontiers in Neurology, 2024)
Background Males with multiple sclerosis (MS) have a higher risk for disability progression than females, but the reasons for this are unclear. Objective We hypothesized that potential differences in TSPO-expressing microglia between female and male MS patients could contribute to sex differences in clinical disease progression. Methods The study cohort consisted of 102 MS patients (mean (SD) age 45.3 (9.7) years, median (IQR) disease duration 12.1 (7.0–17.2) years, 72% females, 74% relapsing–remitting MS) and 76 age- and sex-matched healthy controls. TSPO-expressing microglia were measured using the TSPO-binding radioligand [11C](R)-PK11195 and brain positron emission tomography (PET). TSPO-binding was quantified as distribution volume ratio (DVR) in normal-appearing white matter (NAWM), thalamus, whole brain and cortical gray matter (cGM). Results Male MS patients had higher DVRs compared to female patients in the whole brain [1.22 (0.04) vs. 1.20 (0.02), p = 0.002], NAWM [1.24 (0.06) vs. 1.21 (0.05), p = 0.006], thalamus [1.37 (0.08) vs. 1.32 (0.02), p = 0.008] and cGM [1.25 (0.04) vs. 1.23 (0.04), p = 0.028]. Similarly, healthy men had higher DVRs compared to healthy women except for cGM. Of the studied subgroups, secondary progressive male MS patients had the highest DVRs in all regions, while female controls had the lowest DVRs. Conclusion We observed higher TSPO-binding in males compared to females among people with MS and in healthy individuals. This sex-driven inherent variability in TSPO-expressing microglia may predispose male MS patients to greater likelihood of disease progression.